Repeatability of SUV in Oncologic (18)F-FDG PET - Lodge, Martin A. (J Nucl Med, 2017)
Quantitative analysis can potentially improve the accuracy and consistency of (18)F-FDG PET, particularly for the assessment of tumor response to treatment. Although not without limitations, SUV has emerged as the predominant metric for tumor quantification with (18)F-FDG PET. Growing literature suggests that the difference between SUVs measured before and after treatment can be used to predict tumor response at an early stage. SUV is, however, associated with multiple sources of variability, and to best use SUV for response assessment, an understanding of the repeatability of the technique is required. Test–retest studies involve repeated scanning of the same patient on the same scanner using the same protocol no more than a few days apart and provide basic information on the repeatability of the technique. Multiple test–retest studies have been performed to assess SUV repeatability, although a comparison of reports is complicated by the use of different methodologies and statistical metrics. This article reviews the available data, addressing issues such as different repeatability metrics, relative units, log transformation, and asymmetric limits of repeatability. When acquired with careful attention to protocol, tumor SUV has a within-subject coefficient of variation of approximately 10%. In a response assessment setting, SUV reductions of more than 25% and increases of more than 33% are unlikely to be due to measurement variability. Broader margins may be required for sites with less rigorous protocol compliance, but in general, SUV is a highly repeatable imaging biomarker that is ideally suited to monitoring tumor response to treatment in individual patients.